Effects of light sources and drying methods on plant growth and steviol glycoside content of stevia rebaudiana Bertoni - Rashid, Mohd Aziz; Ding, Phebe; Hassan, Siti Aishah (Malaysian Society of Plant Physiology, 2021)
Stevia (Stevia rebaudiana Bertoni) has received great attention with the rise in demand for low-sugar food and beverage additives, and natural alternative to cane sugar and artificial sweeteners. The leaves produce intensively sweet steviol glycosides (mainly stevioside and rebaudioside A). Stevia has been reported as a short-day plant with a critical day length of 13 h. Day length less than 13 h causes stevia to flower early, resulting in a low leaf biomass yield and percentage of sweetener content. The effects of night interruption treatment using six light sources for 60 min daily with the aim to lengthen vegetative phase, increase plant biomass and steviol glycoside content of stevia were investigated. Night interruption was shown to extend vegetative phase from 20 days (control) to 120 days; thus, allowing accumulation of plant biomass and steviol glycosides content. Leaf biomass and steviol glycosides of all light sources treated plants increased significantly as compared to control plants especially in week 6 and 8 after treatment initiated. Fluorescent and light-emitting diode (LED) were energy-efficient and effective as light source for night interruption. Fluorescent warm white showed the highest increase in total steviol glycosides content per plant by 190-270% most probably because it contained the highest red light at 614 nm as compared to other light sources. Stevioside content was not significantly affected by drying methods but rebaudioside A content was significantly reduced by 3.38% under oven drying at 70oC. The reduction indicated that thermal degradation of rebaudioside A has occurred at higher temperature.